2017
DOI: 10.3390/toxins9120388
|View full text |Cite
|
Sign up to set email alerts
|

T-2 Toxin/HT-2 Toxin and Ochratoxin A ELISAs Development and In-House Validation in Food in Accordance with Commission Regulation (EU) No 519/2014

Abstract: T-2 toxin/HT-2 toxin (T-2/HT-2) and ochratoxin A (OTA) are mycotoxins that can contaminate a variety of agricultural commodities. To protect consumers’ health, indicative limits for T-2/HT-2 and maximum limits for OTA have been set by the European Commission, requiring food business operators and controlling agencies to conduct routine checks for the presence of these harmful contaminants. Screening methods are increasingly used for monitoring purposes. Due to the demand for new and improved screening tools, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
(66 reference statements)
2
15
0
Order By: Relevance
“…657/2002, this parameter has to be lower than 23% and 16% for the fortification levels equal to 100 and 250 μg kg −1 , respectively. This parameter was comparable with the precision of ELISA obtained by Pleadin et al [21], who analyzed the same types of cereals samples investigated in the present study, and higher that that reported by Oplatowska-Stachowiak et al [22] for rye and baby porridge analysis. The recovery percentage was satisfactory as well, since both fortification levels gave a mean value of 102%, whereas the required range set in Decision No.…”
Section: Precision and Recoverysupporting
confidence: 92%
“…657/2002, this parameter has to be lower than 23% and 16% for the fortification levels equal to 100 and 250 μg kg −1 , respectively. This parameter was comparable with the precision of ELISA obtained by Pleadin et al [21], who analyzed the same types of cereals samples investigated in the present study, and higher that that reported by Oplatowska-Stachowiak et al [22] for rye and baby porridge analysis. The recovery percentage was satisfactory as well, since both fortification levels gave a mean value of 102%, whereas the required range set in Decision No.…”
Section: Precision and Recoverysupporting
confidence: 92%
“…Both toxins are produced by moulds that grows on improperly stored grains 12 . HT-2 can cause acute or chronic intoxication of humans and animals 39,40 . The ability to detect low quantities of HT-2 is therefore of great interest for food safety and it can be performed by conventional SPR techniques based on Au with limited sensitivity (~ng/mL) as reported in ref.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory concentration was defined as (1−B/B0) × 100%. Then the half inhibitory concentration (IC 50 , defined as 50% inhibitory concentration), limit of detection (LOD, IC 10 , defined as 10% inhibitory concentration) and detection range (defined as ranged from IC 20 to IC 80 ) were calculated according to the standard curve (Oplatowska‐Stachowiak et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these techniques are hindered by low sample throughput and long analysis time. The immunological methods for TML detection have been used widely in recent years due to their advantages of simple, rapid, and on‐site detection (Deng et al, 2017; Liu, Chu, & Yu, 2016; Oplatowska‐Stachowiak et al, 2017).…”
Section: Introductionmentioning
confidence: 99%